2023
DOI: 10.1029/2022gl102655
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Accessible Air–Water Interfacial Area Accelerates PFAS Leaching in Heterogeneous Vadose Zones

Abstract: Large-scale manufacturing and wide use of Per-and polyfluoroalkyl substances (PFAS) have led to ubiquitous contamination of surface water, soils, sediments, and groundwater (e.g., Brusseau et al., 2020;Johnson et al., 2022). In particular, field investigations have shown that significant amounts of PFAS have accumulated in the vadose zone. Most PFAS are surfactants and experience strong retention in the vadose zone due to adsorption at air-water and solid-water interfaces. While shorter-chain PFAS appear to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Such behavior may be amplified in the presence of heterogeneous soils and preferential flow phenomena. 63 As noted above, the spatial concentration profiles differ for the three groups of PFAS. The asymmetrical, positively skewed profiles observed for the longest-chain PFAS are likely due to the minimal extents of migration observed for these PFAS.…”
Section: ■ Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Such behavior may be amplified in the presence of heterogeneous soils and preferential flow phenomena. 63 As noted above, the spatial concentration profiles differ for the three groups of PFAS. The asymmetrical, positively skewed profiles observed for the longest-chain PFAS are likely due to the minimal extents of migration observed for these PFAS.…”
Section: ■ Discussionmentioning
confidence: 84%
“…Such events produce temporarily large increases in water saturation and correspondingly large decreases in air–water interfacial area, which reduces retention associated with air–water interfacial adsorption. , In addition, porewater velocities are increased, which can lead to increased impacts of mass-transfer kinetics and potential mobile air–water interfaces. , One or more of these factors may contribute to inducing accelerated leaching. Such behavior may be amplified in the presence of heterogeneous soils and preferential flow phenomena …”
Section: Discussionmentioning
confidence: 99%
“…(2018) found that adsorption at the AWI accounted for approximately 50%–75% of the total retention of perfluorooctanoic acid in sand column experiments. Consequently, quantifying the AWI area is critical for accurately modeling the transport and fate of PFAS in environmental systems (Brusseau & Guo, 2022; Zeng & Guo, 2023). 3.…”
Section: Introductionmentioning
confidence: 99%
“…20,36 Later on, the model was also used to investigate the heterogeneity effects in two-dimensional (2D) and three-dimensional (3D) conditions, with results displaying preferential flow caused by subsurface heterogeneity-accelerated leaching of PFAS, especially for long-chain PFAS, and this phenomenon is more prominent than conventional contaminants due to the destruction of AWIs. 35,37 While previous studies above have focused on the vadose zone as a critical source of PFAS contamination, surface water is also a main source contributing to PFAS contamination in the groundwater. 9,38 Surface water and groundwater interact within the hyporheic zone along river corridors.…”
Section: ■ Introductionmentioning
confidence: 99%